Neurolaw between epistemology and ontology:: phenomenology and cognitive neurosciences - Perrotta, Davide (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2021)
In the first part of the paper, I present some problematic concepts in cognitive neuroscience, from a philosophical point of view, like causality and Law. These concepts open ontological questions, that we develop proposing a mechanistic interpretation of cognitive neuroscience, compare to a phenomenological investigation of human experience. General descriptions of mental states and intentionality allow us to investigate different forms of causation, not reducible to “material causes”. By contrast, cognitive neurosciences are specialized to investigate the latter form, being interpretable both like a bound and an advantage. In the second part of the paper we will resort to the presented epistemological descriptions in order to investigate social cognition. We will discuss the case or moral cognition in order to preserve emergent properties in the human experience, in a complementary way with” cognitive mechanisms”. This argumentation will help us to better define the Neurolaw field of researches, allowing us to discern different forms of responsibility of the human acts with regard to different causal factors.